Positive University Environment and Agreeableness as Protective Factors Against Antisocial Behavior in Mexican University Students - Frías Armenta, Martha; Corral-Frías, Nadia S. (Frontiers in Psychology, 2021)
Violence in schools is a global issue. Approximately 32% of Mexican students have experienced some form of violence in the school setting in their lives. Previous research has tended to focus on the causes of violence and antisocial behaviors in offenders or adolescent samples and has found evidence to suggest the underlying role of environmental and personal factors. The present study investigates the effect of positive school environment and agreeableness as protective factors against antisocial behaviors in a sample of undergraduate and graduate students (n=304) from northwestern Mexico. Our results demonstrate that a positive school environment has a negative effect on antisocial behaviors via mood and anxiety disorders as well as in interaction with agreeableness, suggesting an interplay between personality and environment. These findings can provide some basis for the development of university programs aimed at fostering positive environments that promote student mental health and protect against antisocial behaviors.